FINANCIAL WELLNESS OF STUDENTS IN EAST JAVA: THE ROLE OF PARENTAL FINANCIAL EDUCATION, FINANCIAL STATUS, FINANCIAL LITERACY, AND FINANCIAL BEHAVIOR - Asiah, Afifah Nur; Haryono, Agung; Churiyah, Madziatul (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This study aims to identify the factors influencing the financial wellness of students in East Java. The factors examined include parental financial education, financial status, financial literacy, and financial behavior. This research employs a quantitative approach involving 384 students from various universities in East Java. Data were collected through a questionnaire adapted from previously validated instruments. Data analysis was conducted using Structural Equation Modelling – Partial Least Square (SEM-PLS) to determine the influence of each variable on students' financial wellness. The results indicate that parental financial education, financial status, financial literacy, and financial behavior have a significant positive impact on students' financial wellness. Additionally, parental financial education and financial status significantly contribute to students' financial behavior. Meanwhile, financial literacy does not affect students' financial behavior. This suggests that financial behavior mediates the relationship between parental financial education, financial status, and financial wellness.